Too much is not enough : a memoir of fumbling toward adulthood - Rannells, Andrew (Crown Archetype, 2019)
"From the star of Broadway's The Book of Mormon and HBO's Girls, the heartfelt and hilarious coming-of-age memoir of a Midwestern boy surviving bad auditions, bad relationships, and some really bad highlights as he chases his dreams in New York City."--Publisher's description.